Sarod-i ġaybī musammā bah H̱ayābān-i tavārīẖ : ẖazīnah-i ṣanʿat, tavārīẖ-i ʿajab, camanistān-i farḥat, nigāristān-i bahjat - Murādābādī, Muḥammad ʿAlī Jūyā Saiyid (Navalkišor, 1881)
Treatise on the numerological derivation of historical dates, using, for example, the abjad values of the names of prophets, poets and historical figures; numerological values hidden in couplets